Phenological Variation and its Relation with Yield in several Wheat (Triticum aestivum L.) Cultivars under Normal and Late Sowing Mediated Heat Stress Condition - Kamrun NAHAR; Kamal Uddin AHAMED; Masayuki FUJITA (Notulae Scientia Biologicae, 2010)
Phenological performance in relation to yield of five modern varieties of wheat Sourav, Pradip, Sufi, Shatabdi and Bijoy were evaluated under two growing environments; one is normal growing environment (sowing at November 30) and the other is post anthesis heat stressed environment (sowing at December 30). In case of late seeding, the varieties phased a significant level of high temperature stress that also significantly affected the required days to germination, booting, anthesis, maturity of all varieties including the yield as compared to normal sowing treatment. The temperature during the grain filling or grain maturing period was near 23C in case of normal seeding and it was near about 28C to 30C and sometimes reached above this range in the later period of late seeded treatment. In the normal sowing treatment the germination period was lower than the late sowing treatment as during that time the temperature was higher as compared to late sowing condition where temperature was lower. Days to anthesis and booting decreased due to late sown heat stress condition regardless the cultivars. These phenological characteristics under heat stressed condition led the wheat cultivars to significantly lower the grain yield as compared to normal condition. Due to heat stress, the yield reduction was 69.53% in Sourav, 58.41% in Pradip, 73.01% in Sufi, 55.46% in Shatabdi and 53.42% in Bijoy.